Pengaruh Costumer Experience Terhadap Brand Loyalty Pada Mie Gacoan Cabang Dr. Mansyur Medan - Mita Fasya; Jennifer Tio; William Dika Manihuruk; Meichell Topan Panjaitan; Rendy Gultom; Onan Marakali Siregar; Afrila Mulyati Siregar (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to examine the influence of customer experience on brand loyalty at the Gacoan Noodle outlet, the Dr. Mansyur Medan branch. A marketing strategy that focuses on long-term relationships with long-term relationships with customers, as well as the importance of customer experience and brand loyalty, are the main concerns in this study. Loyalty are the main concerns in this study. The research method used the research method used is quantitative with simple linear regression analysis techniques. Data was collected through distributing questionnaires to 100 respondents who have transacted at transactions at the Mie Gacoan outlet, Dr. Mansyur Medan branch. Research results the results showed that all questionnaire items were valid and reliable. Simple linear regression results regression results show that customer experience has a positive and significant influence on brand loyalty. Thus, increasing customer experience canincrease Brand Loyalty at the Dr. Mansyur Medan Branch of Gacoan Noodle Shop.